The Millennium Development Goals: A Latin American and Caribbean Perspective - José Luis Machinea, Alicia Bárcena, Arturo León (My University, 2016)
Document covers the question of inequality within the region of Latin America and Caribbean and attempts to find solutions by clearly identifying the problem and providing appropriate measures to solve them.